(untitled) (Journal of Plant Disease Sciences, 2023)
A field experiment was undertaken on clay loam soil of Sorghum Research Unit, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola (Maharashtra). An experiment was laid out in the factorial randomized block design in three replications. There were twelve treatment combinations consisting of three different levels of RDF viz., F1 - 50% RDF, F2 -75% RDF, F3 -100% RDF (80:40:40 kg/ha of N:P2O5:K2O) and four seed treatments viz., S1 -Control (without seed treatment and only application of fertilizer), S2 - seed treatment with Azospirillum brasilense and phosphate solubilizing bacteria @ 25 g each/kg seed, S3 - seed treatment with liquid Azospirillum brasilense and phosphate solubilizing bacteria @ 2 ml each/kg seed and S4 - seed treatment with liquid Azospirillum brasilense and phosphate solubilizing bacteria @ 4 ml each/kg seed. Application of 50% RDF recorded significantly higher rhizospheric